Romania : First and Second Reviews Under the Stand-By Arrangement and Requests for Waiver of Nonobservance of a Performance Criterion, Modification of Program conditionality, and Rephasing of the Availability Dates of Purchases. (IMF Staff Country Reports; Country Report, 2014)
This first and second reviews under the Stand-By-Arrangement analyzes Ex Post Evaluation of exceptional access for Romania. Efforts are needed to strengthen monetary policy transmission. The banking system remains well capitalized, but the authorities need to accelerate the resolution of nonperforming loans and closely monitor risks from parent bank deleveraging. The Romanian authorities continue their efforts to reach the goals of a broad structural agenda, with a focus on structural reforms in the energy, transport and healthcare sectors, and continue the reform of the state-owned enterprises.